Improving Pressure Steam Sterilization Quality Through Healthcare Failure Mode and Effects Analysis: A Pre-Post Intervention Study in Central Sterile Supply Departments - Zhang Y; Hu R; Chen Y; Liu X; Wu J; Yi L (Risk Management and Healthcare Policy)
Yanrong Zhang,1,2 Ruixue Hu,1,2 Yanhua Chen,1,2 Xiaoxiao Liu,1,2 Jin Wu,1,2 Liangying Yi1,2 1Department of Sterile Processing Nursing, West China Second University Hospital, Sichuan University, Chengdu, Sichuan, People’s Republic of China; 2Key Laboratory of Birth Defects and Related Diseases of Women and Children (Sichuan University), Ministry of Education, Chengdu, Sichuan, People’s Republic of ChinaCorrespondence: Liangying Yi, Department of Sterile Processing Nursing, West China Second University Hospital, Sichuan University, No. 20 Section 3, South Renmin Road, Chengdu, Sichuan, 610041, People’s Republic of China, Email yiliangying88@163.comObjective: To evaluate the effectiveness of Healthcare Failure Mode and Effects Analysis (HFMEA) in reducing quality defects during pressure steam sterilization in the Central Sterile Supply Department (CSSD).Methods: The study followed a structured HFMEA framework: (1) A multidisciplinary team (n=7) with CSSD expertise was established to analyze sterilization workflows, including instrument scanning, sterilization verification, and post-sterilization cooling. (2) Process mapping and risk prioritization were conducted using a 4-level severity/occurrence matrix (adapted from Australian clinical risk criteria) to calculate Risk Priority Numbers (RPN=Severity×Occurrence). High-risk failure modes (RPN≥ 8 or severity=4) were identified, including unlabeled “non-sterilized” packages (due to incomplete scanning), wet packages (from insufficient cooling< 30 minutes), and unverified sterilization information. (3) Root causes were analyzed via fishbone diagrams (human, machine, material, environment, method). Targeted interventions included: optimizing the traceability system with department-specific alerts, standardizing scanning protocols, staff retraining on verification procedures, increasing instrument inventory and sterilizer racks, and implementing performance monitoring with 5W1H checklists.Results: Pre-intervention, 87 defects were identified among 185,382 sterilization packages (32 unlabeled “non-sterilized”, 10 wet packages). Post-intervention, defects decreased to 11/189,531 packages (χ²=115.556, P< 0.001), including 4 unlabeled (χ²=374.951, P< 0.001) and 2 wet packages (χ²=8.889, P=0.003).Conclusion: Systematic HFMEA application reduced sterilization defects by addressing critical workflow gaps, demonstrating its value in enhancing CSSD quality control and patient safety.Keywords: healthcare failure mode and effects analysis, central sterile supply department, pressure steam sterilization, quality defects